Aplikasi Peminjaman Warkah sebagai Pendukung Tertib Administrasi Arsip di Kantor Pertanahan Kabupaten Ponorogo - Shasya Aninda Fahliza; Izzatul Ulya (Advances In Education Journal, 2026)
The management of borrowing and returning land document files (warkah) at the Land Office of Ponorogo Regency was initially conducted through manual recording, resulting in difficulties in document traceability, unclear status, and potential administrative errors. This study aims to develop and implement a Microsoft Access–based borrowing application to support orderly archival administration. The research employed an action research approach with data collected through observation, interviews, document analysis, and system testing during implementation. The results indicate that the application improves structured recording, accelerates document retrieval, clarifies file status, and reduces recording errors. These changes strengthen administrative control and enhance accountability in archival management. The study concludes that a simple, user-oriented information system can effectively support orderly archival administration and provide a practical model for improving document management practices in similar governmental institutions.